Identification of a temperature-sensitive mutation in the htpR (rpoH) gene of Escherichia coli K-12. - Waghorne, C (1985)
A new mutation in the htpR (rpoH) gene of Escherichia coli K-12 was identified. The mutation resulted in a temperature-sensitive phenotype in terms of cell growth and bacteriophage lambda development. As in the case of the classical htpR tsn-165 mutation, synthesis of heat shock polypeptides was not induced in strains carrying the mutation described here.